2020
DOI: 10.1128/jvi.02039-19
|View full text |Cite
|
Sign up to set email alerts
|

Two Functional Variants of AP-1 Complexes Composed of either γ2 or γ1 Subunits Are Independently Required for Major Histocompatibility Complex Class I Downregulation by HIV-1 Nef

Abstract: The HIV-1 accessory protein Nef downregulates the cell surface expression of major histocompatibility complex class I (MHC-I) molecules to facilitate virus spreading. The Nef-induced downregulation of MHC-I molecules such as HLA-A requires the clathrin adaptor protein 1 (AP-1) complex. The cooperative interaction of Nef, AP-1, and the cytosolic tail (CT) of HLA-A leads to a redirection of HLA-A targeting from the trans-Golgi network (TGN) to lysosomes for degradation. Although the γ-adaptin subunit of AP-1 has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 56 publications
3
13
0
Order By: Relevance
“…This protocol was based on a previous paper by Perez-Victoria ( 22 , 46 ). HEp-2 cells were infected with HRSV (MOI = 1).…”
Section: Methodsmentioning
confidence: 99%
“…This protocol was based on a previous paper by Perez-Victoria ( 22 , 46 ). HEp-2 cells were infected with HRSV (MOI = 1).…”
Section: Methodsmentioning
confidence: 99%
“…The relatively weak interaction between nef and tetherin reduces AP1's ability to recruit clathrin, leading to retention of tetherin at the TGN, while the strong nef-MHCI interaction promotes AP1 clathrin binding that subsequently targets MHCI for lysosomal degradation [48]. Supporting this model, Tavares et al reported that HIV nef interacts with both 1 and 2 forms of AP1 to deplete MHCI from the PM [50].…”
Section: Cargo Transport Pathways: Roles In Development and Diseasementioning
confidence: 97%
“…As previously mentioned, the clathrin adaptor AP-1 is recruited by ARF-1 to TGN membranes to form clathrin-coated vesicles (CCVs) that are destined for endosomes. In fact, MHC-I downregulation by Nef was shown to require AP-1 ( Williams et al, 2002 ; Roeth et al, 2004 ; Lubben et al, 2007 ; Schaefer et al, 2008 ; Leonard et al, 2011 ; Jia et al, 2012 ; Tavares et al, 2020 ) and ARF-1 activity ( Wonderlich et al, 2011 ). Structural analysis revealed that ARF-1-GTP binding to AP-1 triggers conformational changes in AP-1, which acquires an ‘unlocked’ state that is compatible with vesicle-cargo binding ( Ren et al, 2013 ).…”
Section: Hiv-1 Accessory Proteinsmentioning
confidence: 99%
“…In fact, the expression of an ARF-1 dominant-negative form inhibited Nef-CD4 complex migration toward the lysosome ( Fauré et al, 2004 ), highlighting the importance of ARF-1 in other receptor downregulation strategies utilized by Nef. Interestingly, it has been shown that Nef uses a variant of AP-1 (AP-1-γ2) to retain CD4 ( Tavares et al, 2017 ) and MHC-I ( Tavares et al, 2020 ) in endosomes for lysosomal delivery.…”
Section: Hiv-1 Accessory Proteinsmentioning
confidence: 99%